Prevalence of small t trauma in depressed adolescent and early adulthood patient in King Chulalongkorn Memorial Hospital - Thongrakyoo, Krittapast; Laurujisawat, Puchong; Chandarasiri, Parichawan (Chulalongkorn Medical Journal, 2023)
Background: Trauma and depression are known to be related, especially in adolescents and early adulthood patients in which depression usually starts, then deteriorates, and causes decreased function and worse quality of life. Objective: To study prevalence of small t trauma level in adolescents and early adulthood patients with depression and to determine whether the level of small t trauma and severity of depression are associated. Methods: This cross-sectional descriptive study recruited depressive patients aged 15 - 25 years to complete a questionnaire consisting of three parts: demographic data and big T trauma, Beck Depression Inventory-IA scale Thai version, and the small t trauma level of adverse childhood experience. Results: One hundred and six subjects were recruited in this study. Majority of them had high small t trauma level (66.0% in the red zone) and had severe depression. Furthermore, the level of the small t trauma was positively correlated with the severity of depression (r = 0.25, P = 0.02). Conclusion: The subjects had high small t trauma level and had severe depression which both were related. Therefore, this risk should be concerned in child rearing, educational system, and mental health promotion of children and adolescent.